Antecedents of Green Purchasing Behaviour and Selection Criteria among Generation Y and Z Consumers - Aryal, Dipesh; Tamang, Govinda (Journal of Business and Social Sciences Research, 2024)
The research explores how factors influencing green purchasing behaviour and selection attributes shape the green purchasing patterns of Gen Y and Gen Z consumers. Data was collected from 384 respondents aged 19-43 through a self-administered, close-ended questionnaire on Google Forms. A 30-item questionnaire measured seven key variables in the study. Results indicate that environmental concern, government influence, social influence, environmental attitude, and environmental responsibility have significant impacts on green purchasing behaviour within these generational groups and selection attribute moderate the relationship between green purchasing behaviour and its antecedents. Grounded in the theories of planned behaviour, reasoned action, and consumption values, this study enriches the understanding of factors driving sustainable purchasing among younger consumers, especially in developing countries like Nepal. These insights can help businesses and policymakers create targeted strategies to inspire Gen Y and Gen Z consumers toward more sustainable choices.